Interrogantes sobre genealogía y dinámicas de la ciudadanía - Pompejano, Daniele (Pontificia Universidad Católica del Perú. Fondo Editorial, 2006)
The main hypotesis of this article relys on the Colonial social relationship and the neoclassicists philosophy as the roots of Latin America authoritarian rule. From the concept of “natural” human being, patronizing and clientelism drove to an asymmetric relationship between authority and individuals within a corporative society. Although the Borbonism and liberalism had been strong dynamic forces, they were unsuccessful for changing such scheme and only a secularization process could timidly be carried on. For consequence, the Latin America politic modernization went on an authoritarian way, turning to populism, whereas individual became subaltern of the State; so, citizenship become indefinitely postponed.

La filosofía neoclásica y las relaciones sociales coloniales como raíces del autoritarismo latinoamericano conforman la hipótesis central de este trabajo. El ser natural como conceptualización del individuo condujo a una relación asimétrica entre la autoridad y los individuos en el contexto de una sociedad corporativa. Aunque el borbonismo y el liberalismo habían sido fuerzas dinámicas poderosas, no tuvieron éxito para cambiar el esquema, salvo, aunque tímidamente, en la secularización. Por tanto, la modernización política en América continuó bajo un autoritarismo que tomó forma de populismo, donde el individuo queda subordinado al estado; de esta forma, el concepto de ciudadanía queda pospuesto indefinidamente.
Keywords: Economía; Genealogía; Ciudadanía; América Latina; Liberalismo; Autoritarismo; Sociedad; Economic Thinking; Macroeconomic Theory; Is-Lm Model; https://purl.org/pe-repo/ocde/ford#5.02.01